A experimentação no curso de licenciatura em Química da UFSCar (campus São Carlos): aproximações e distanciamentos à química verde - Tasso, João Francisco Nunes (Universidade Federal de São Carlos, 2018)
The introduction of Green Chemistry in university subjects has occurred mainly through experimental proposals in teaching laboratories in the last twenty years. For this reason, the objective of this work was to investigate how the principles of the Green Chemistry (GQ) philosophy are inserted in the laboratory practices present in the documents related to the undergraduate course in Chemistry of UFSCar of the São Carlos campus. Through this case study, we sought to analyzed the approaches and distances of the experimental disciplines to the GQ. We analyzed the official documents ("Guidelines and Bases of National Education", "National Curriculum Guidelines for Chemistry, Bachelor's and Master's degree courses", "National Curricular Guidelines for the Training of Basic Education Teachers at the higher level, undergraduate course", "CNE / CES 8 Resolution", "Institutional Development Plan", "Profile of the professional to be graduated at UFSCar", "Pedagogical projects" and the respective course curriculum which is composed of seven compulsory experimental subjects). The methodology of data collection and analysis is qualitative, the latter based on the Discursive Textual Analysis, whose purpose is to produce new understandings about the object of study and the discourses that compose it. After the analysis of the data the category "Education in Green Chemistry" (GQE), was elaborated and it contains the subcategory "Green Experimentation". The analysis of how GQE is inserted in the official documents is expressed through the understandings about the CTSE relations and of inter / multi / pluri / transdisciplinary contents, of the GQ, of the sustainability and of the curricular environmentalization present in these documents. Therefore, we observe that the curriculum has the potential to understand the plurality in the formation of the graduating and supports the necessary contextualization of the contents, transversality and social and ethical issues, aspects closely related to GQE. The Green Experimentation aims to bring to the experimental practices the historical aspects of knowledge production and to bring students closer to the philosophy of GQ through the principles and principles of Green Chemistry Education (GCEP). In the analysis of the menus of the seven experimental disciplines, we observe that there are distances from some present understandings, such as the instrumental character attributed to experimentation. The content "waste treatment and disposal" is recurrent in the experimental practices and in a more significant way as a punctual and remediation activity, that distances itself from a Green Experimentation. In a less expressive way, other discourses are being constructed on the minimization and elimination of residues, and have a closer approximation to Green Experimentation.
Keywords: Educação em Química Verde; Experimentação; Formação inicial de professores de Química; Green Chemistry Education; Experimentation; Initial training of chemistry teachers; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS